Alarming rates of virological failure and HIV‐1 drug resistance amongst adolescents living with perinatal HIV in both urban and rural settings: evidence from the EDCTP READY‐study in Cameroon. Issue 7 (31st March 2021) - Fokam, J; Takou, D; Njume, D; Pabo, W; Santoro, MM; Njom Nlend, A‐E; Beloumou, G; Sosso, S; Moudourou, S; Teto, G; Dambaya, B; Djupsa, S; et al.
Abstract : Objectives: Adolescents living with perinatal HIV infection (ALPHI) experience persistently high mortality rates, particularly in resource‐limited settings. It is therefore clinically important for us to understand the therapeutic response, acquired HIV drug resistance (HIVDR) and associated factors among ALPHI, according to geographical location. Methods: A study was conducted among consenting ALPHI in two urban and two rural health facilities in the Centre Region of Cameroon. World Health Organization (WHO) clinical staging, self‐reported adherence, HIVDR early warning indicators (EWIs), immunological status (CD4 count) and plasma viral load (VL) were assessed. For those experiencing virological failure (VF, VL ≥ 1000 copies/mL), HIVDR testing was performed and interpreted using the Stanford HIV Drug Resistance Database v.8.9–1. Results: Of the 270 participants, most were on nonnucleoside reverse transcriptase inhibitor (NNRTI)‐based regimens (61.7% urban vs . 82.2% rural), and about one‐third were poorly adherent (30.1% vs . 35.1%). Clinical failure rates (WHO‐stage III/IV) in both settings were < 15%. In urban settings, the immunological failure (IF) rate (CD4  < 250 cells/μL) was 15.8%, statistically associated with late adolescence, female gender and poor adherence. The VF rate was 34.2%, statistically associated with poor adherence and NNRTI‐based antiretroviral therapy. In the rural context, the IF rate was 26.9% and the VF rate was 52.7%, both statistically associated with advanced clinical stages. HIVDR rate was over 90% in both settings. EWIs were delayed drug pick‐up, drug stock‐outs and suboptimal viral suppression. Conclusions: Poor adherence, late adolescent age, female gender and advanced clinical staging worsen IF. The VF rate is high and consistent with the presence of HIVDR in both settings, driven by poor adherence, NNRTI‐based regimen and advanced clinical staging.